1980
DOI: 10.2737/pnw-rp-277
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the export and import of raw logs on domestic timber supplies and prices.

Abstract: This file was created by scanning the printed publication. Mis-scans identified by the software have been corrected; however, some errors may remain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The three scenarios were a direct tradeoff between logs restrained and lumber export expanded: (1) no tradeoff-Japan would not substitute North American lumber for logs; (2) Japan would substitute Canadian but not U.S. lumber for the logs foregone; and (3) a mixed scenario in which Japan would fully offset with North American lumber, with half each from Canada and the United States but with no expansion of Northwest milling capacity. 424 Darr noted in 1980 that Portland, Oregon's, chamber of commerce had, in 1936, objected to the export of Port-Orford-cedar, which demonstrated a long history of opposition by some to timber trade. Reflecting on some trade-limiting proposals, he suggested that proponents consider six questions: How much of the log volume that would have been exported would instead be processed?…”
Section: Global Forestry Issues and International Tradementioning
confidence: 99%
“…The three scenarios were a direct tradeoff between logs restrained and lumber export expanded: (1) no tradeoff-Japan would not substitute North American lumber for logs; (2) Japan would substitute Canadian but not U.S. lumber for the logs foregone; and (3) a mixed scenario in which Japan would fully offset with North American lumber, with half each from Canada and the United States but with no expansion of Northwest milling capacity. 424 Darr noted in 1980 that Portland, Oregon's, chamber of commerce had, in 1936, objected to the export of Port-Orford-cedar, which demonstrated a long history of opposition by some to timber trade. Reflecting on some trade-limiting proposals, he suggested that proponents consider six questions: How much of the log volume that would have been exported would instead be processed?…”
Section: Global Forestry Issues and International Tradementioning
confidence: 99%
“…Expanding lumber production was predicted to lead to greater Canadian gains from trade, especially after forest managers accessed untapped timber resources and used more intensive timber management strategies. Projections estimated that Canadian softwood lumber output would double to 22 billion board feet from 1975 to 2000 (Darr et al 1980). By the end of the 1970s, U.S. imports of Canadian lumber had doubled.…”
Section: Us Dollars (Billions)mentioning
confidence: 99%